2017
DOI: 10.1111/bph.13769
|View full text |Cite|
|
Sign up to set email alerts
|

Hippocampal α7 nicotinic ACh receptors contribute to modulation of depression‐like behaviour in C57BL/6J mice

Abstract: This article is part of a themed section on Nicotinic Acetylcholine Receptors. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v175.11/issuetoc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 69 publications
3
50
0
Order By: Relevance
“…It is important to note that α7 nAChRs have also been implicated in nicotine withdrawal‐associated anhedonia (Stoker et al, ), which is clinically relevant as it constitutes a motivational trigger to relapse. Even more intriguingly, recent data points specifically to the hippocampal α7 nAChRs as key modulators of negative affect (Mineur et al, ) which makes our hypothesis for a direct link between the protective effect of exercise on the negative consequences of nicotine abstinence and α7 hippocampal up‐regulation even more appealing. It is of course impossible to know based on the current study whether those up‐regulated receptors are desensitized or active and if these lead to downstream adaptations that may protect the development of physical dependence.…”
Section: Discussionmentioning
confidence: 84%
“…It is important to note that α7 nAChRs have also been implicated in nicotine withdrawal‐associated anhedonia (Stoker et al, ), which is clinically relevant as it constitutes a motivational trigger to relapse. Even more intriguingly, recent data points specifically to the hippocampal α7 nAChRs as key modulators of negative affect (Mineur et al, ) which makes our hypothesis for a direct link between the protective effect of exercise on the negative consequences of nicotine abstinence and α7 hippocampal up‐regulation even more appealing. It is of course impossible to know based on the current study whether those up‐regulated receptors are desensitized or active and if these lead to downstream adaptations that may protect the development of physical dependence.…”
Section: Discussionmentioning
confidence: 84%
“…Consistent with this hypothesis, nAChR antagonists have some efficacy in animal models of depression. Picciotto and colleagues explored the role of α7 nAChRs in the hippocampus in anxiety‐like and depression‐like behaviours in mice (Mineur et al ., ). Pharmacological antagonism or local knockdown of α7 nAChRs (using short hairpin RNAs) produced some significant amelioration in certain mouse models but, intriguingly, also revealed some striking gender differences.…”
Section: Discussionmentioning
confidence: 97%
“…Smokers, although abstinent for several years, are threefold more likely to develop mood disorders (Breslau & Johnson, 2000); smoking as a coping strategy is highly prevalent in patients suffering from mood disorders. The role of nAChRs in mood disorders has been investigated in humans (Saricicek et al, 2012) and confirmed in animal models (Mineur et al, 2016(Mineur et al, , 2017. VTA DA neurons do not only encode positive reinforcement and reward, but also for negative and salient events, promoting adaptive behaviors.…”
Section: Alteration Of Non-drug Functions Of Vta Da Neuronsmentioning
confidence: 97%